The Role of Social Media Advertising Value and Technology Acceptance Influence on Purchasing to Supplementary Food Product Through Online Channel of Young Elderly - Nurittamont, Wasutida; Leehuad, Sornnarin; Samleete, Kanchanawadee (RMUTI Journal Humanities and Social Sciences, 2026)
The objectives of this study were to investigate the influence of social media advertising value on the purchasing to supplementary food product through online channel of young elderly and to examine the impact of technology acceptance on the purchasing to supplementary food product through online channel of young elderly. Online questionnaires were used to collect data from 395 participants, employing non-probability sampling through convenience sampling method. The data analysis included descriptive statistics such as percentage, frequency, average, and standard deviation. Hypothesis testing was conducted using multiple regression analysis with the Enter method. The results revealed that advertising on social media, particularly in terms of entertainment, informativeness, and credibility, positively influences the intention to purchase online of young elderly. Additionally, technology acceptance, particularly perceived usefulness, has a positive effect on the intention to purchase online of young elderly. Therefore, the findings of this study can serve as guidelines for promoting the development of marketing communications tailored to the needs and behaviors of young elderly using technology.